PENGARUH KARAKTERISTIK PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INFORMASI - MEIRYANANDA PERMANASARI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The purpose of this study is to investigate the relationship between firm’s characteristics and corporate governance mechanisms on disclosure. This study used a sample of 100 (one hundred) public listed company on the Indonesia Stock Exchange. Categorized into 2 (two) groups of industry, they are property-real estate industry, and trade, services and investment industry. The results of this study indicate that the company's capital structure, as reflected by the debt to equity ratio has no influence on disclosure. When analyzed partially, the result shows that the debt to equity ratio has no effect on both groups. The ability of the company in generating profits as reflected by the net profit margin has no effect on disclosure. Mean while the company's size as reflected by the total assets has a positive effect on disclosure. Tested partially, it also affect on both types of industry. Institutional ownership has negative effect on disclosure, when tested partially, the result shows that both industries have negative effect on disclosure. Management ownership has negative effect on disclosure, especially on property and real estate industry. The percentage of independent commissioners has no effect on disclosure but when tested partially it has a negative effect on trade, services, and investment group. The last, audit committee has no effect on disclosure.